2006
DOI: 10.1542/peds.2005-1063
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Decision Rule to Predict Need for Computed Tomography Among Children With Blunt Head Trauma

Abstract: OBJECTIVE. To assess the ability of the NEXUS II head trauma decision instrument to identify patients with clinically important intracranial injury (ICI) from among children with blunt head trauma.METHODS. An analysis was conducted of the pediatric cohort involved in the derivation set of National Emergency X-Radiography Utilization Study II (NEXUS II), a prospective, observational, multicenter study of all patients who had blunt head trauma and underwent cranial computed tomography (CT) imaging at 1 of 21 eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 30 publications
3
74
0
4
Order By: Relevance
“…15,23 Head injury occurring during a sporting activity has consistently failed to be identified as a risk factor for an abnormal CT finding across pediatric studies, which includes other risk factors such as low Glasgow Coma Scale score; suspected open, depressed, or basal skull fractures; persistent headache or irritability; large or boggy scalp hematoma; and dangerous mechanism of injury (i.e., motor vehicle accident, fall from bicycle with no helmet). 3,16,24,27,[35][36][37] These studies have informed the development of several clinical decision rules that help guide the judicious use of CT imaging in pediatric patients with mTBI who are evaluated in the emergency department. 3,16,24,27,[35][36][37] In the present study, 21% of CT imaging studies performed by emergency department physicians in patients with suspected SRC demonstrated abnormal findings, including calvarial skull fracture (1 patient), orbital floor fracture (1 patient), suspected ICH (2 patients), and posterior fossa arachnoid cyst (1 patient).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,23 Head injury occurring during a sporting activity has consistently failed to be identified as a risk factor for an abnormal CT finding across pediatric studies, which includes other risk factors such as low Glasgow Coma Scale score; suspected open, depressed, or basal skull fractures; persistent headache or irritability; large or boggy scalp hematoma; and dangerous mechanism of injury (i.e., motor vehicle accident, fall from bicycle with no helmet). 3,16,24,27,[35][36][37] These studies have informed the development of several clinical decision rules that help guide the judicious use of CT imaging in pediatric patients with mTBI who are evaluated in the emergency department. 3,16,24,27,[35][36][37] In the present study, 21% of CT imaging studies performed by emergency department physicians in patients with suspected SRC demonstrated abnormal findings, including calvarial skull fracture (1 patient), orbital floor fracture (1 patient), suspected ICH (2 patients), and posterior fossa arachnoid cyst (1 patient).…”
Section: Discussionmentioning
confidence: 99%
“…3,16,24,27,[35][36][37] These studies have informed the development of several clinical decision rules that help guide the judicious use of CT imaging in pediatric patients with mTBI who are evaluated in the emergency department. 3,16,24,27,[35][36][37] In the present study, 21% of CT imaging studies performed by emergency department physicians in patients with suspected SRC demonstrated abnormal findings, including calvarial skull fracture (1 patient), orbital floor fracture (1 patient), suspected ICH (2 patients), and posterior fossa arachnoid cyst (1 patient). One patient was found to have a normal anatomical variant of the septum pellucidum, including a cavum septum pellucidum and a cavum vergae, which was classified as a normal finding and is present in up to 20% of the general pediatric population on neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been conducted in the past 10 years to identify a set of high-risk findings that would clearly indicate which children with minor head injury should undergo CT. [29][30][31][32][33][34] Unfortunately, those studies have been highly variable in design, and few could be considered robust according to methodologic standards for the development of clinical decision rules. 11 Interestingly, all of the clinical variables that Note: CI = confidence interval, NA = not applicable, OR = odds ratio, SD = standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…19 Porém, a especificidade desse sintoma na predição de lesão intracraniana é baixa, especialmente em crianças abaixo de 3 anos de idade. 26 Alguns autores relacionam a presença de VPTCE como fator de risco de lesão intracraniana em pacientes com nível de consciência preservado. 27,28 Nosso trabalho está de acordo com outros autores para os quais episódio de vômito isolado pós-TCE não é fator de risco independente.…”
Section: De Acordo Com O Mild Trauma Brain Injury Committee Of the Heunclassified